Kyrgyzstan under new leadership: Path to a better future? - Beate Eschment (Stiftung Wissenschaft und Politik (SWP), 2005)
By mid-September 2005 disquieting reports were coming one after another out of Kyrgyzstan: the dismissal of the federal prosecutor who had vigorously gone after the widespread corruption; the murder of an MP; an emergency session of the parliament. These events contradict earlier expectations that calm would return to the country after Kurmanbek Bakiyev had been elected for president on 10 July with a surprisingly high 89 percent of the popular vote and had been inaugurated on 14 August 2005 with much fanfare. Germany and Western Europe badly need allies in the strife-ridden region around Kyrgyzstan. And Kyrgyzstan is the only state in the region in which relative political liberty exists and where Islamic fundamentalism, at least up to the moment, does not have significant influence. (SWP-Comments / SWP)
Keywords: 320